Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1159/000445170
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Therapy of Brain Edema after Intracerebral Hemorrhage

Abstract: Background: Intracerebral hemorrhage (ICH) is a subtype of stroke with a severe high mortality and disability rate and accounts for about 10-15% of all strokes. The oppression and destruction by hematoma to brain tissue cause the primary brain injury. The inflammation and coagulation response after ICH would accelerate the formation of brain edema around hematoma, resulting in a more severe and durable injury. Currently, treatments for ICH are focusing on the primary injury including reducing intracranial hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
165
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(185 citation statements)
references
References 112 publications
1
165
0
9
Order By: Relevance
“…12,30 Microglia have multiple capabilities that can critically impact hemorrhagic brain injury, including the production of proinflammatory cytokines. 6,31 Recent studies have demonstrated that activation of microglia contributes to brain injury after ICH 30,[32][33][34] and that removal of microglia attenuates hemorrhagic brain injury. 19 In line with these findings, ICH triggered a predominant expression of the transcriptor AP-1 in microglia in conjunction with upregulation of IL-6 and TNF-α, well-known proinflammatory cytokines that amplify local inflammation, further supporting a detrimental role of microglia in acute ICH injury.…”
Section: Discussionmentioning
confidence: 99%
“…12,30 Microglia have multiple capabilities that can critically impact hemorrhagic brain injury, including the production of proinflammatory cytokines. 6,31 Recent studies have demonstrated that activation of microglia contributes to brain injury after ICH 30,[32][33][34] and that removal of microglia attenuates hemorrhagic brain injury. 19 In line with these findings, ICH triggered a predominant expression of the transcriptor AP-1 in microglia in conjunction with upregulation of IL-6 and TNF-α, well-known proinflammatory cytokines that amplify local inflammation, further supporting a detrimental role of microglia in acute ICH injury.…”
Section: Discussionmentioning
confidence: 99%
“…The latter concept is explained as the cause of the most characteristic posterior reversible encephalopathy syndrome (PRES) lesion. In hypertensive encephalopathy, brain edema can cause stimulation of stretch receptors in the fourth ventricle, which can make the hypertension worse8). These theories suggest that hypertensive encephalopathy can have different characteristics depending on the underlying diseases, because each etiology has a different contributing factor for hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Brain atrophy may also contribute to a larger hematoma volume on presentation because of a less effective tamponade effect [9,26] . Additional damage might derive from an excess of local neuroinflammatory response due to dysregulation of aging microglia [31] possibly through acceleration in the formation of brain edema [32] . We actually observed a wide range of values for admission hematoma volume in oldest-old subjects and data dispersion was already noticeable for the old-old.…”
Section: Discussionmentioning
confidence: 99%